Victim compensation: a child of penal welfarism or carceral policies - Mimi E. Kim; Carina Gallo (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Swedish Under efterkrigstiden förändrades många västerländska länders kriminalpolitik i riktning mot välfärd och rehabilitering. Detta ideal fokuserade gärningsmannen, inte brottsoffret. Detta skulle snart komma att förändras. En av de första initiativ som togs för brottsoffer var brottsskadeersättning, en ekonomisk kompensation som infördes på 1960-talet. Denna artikel jämför utvecklingen av brottsskadeersättning i två länder, USA och Sverige, i relation till deras välfärds- och kriminalpolitik. Båda länderna initierade kompensationsreformer för brottsoffer i välfärdsinstitutionella kontexter. Med stöd i en jämförande historisk fallstudiemetod visar artikeln dock att kompensationsreformerna i de två länderna skilde sig åt och kom att avspegla respektive lands välfärds- och kriminalpolitik. De första svenska kompensationsreformerna förankrades som en socialförsäkringsfråga, medan deras motsvarigheter i USA snabbt banade väg för mer straffinriktade program. Abstract English In the post-war period, many Westernized countries advanced toward more rehabilitative and welfarist ideals informing crime policies. These ideals centered on the offending individual, not the victim. This was soon to change. Victim compensation programs were one of the first initiatives taken for victims of crime with the first established in the 1960s. This paper examines and compares the development of victim compensation programs in two countries with contrasting social welfare and penal policies, the United States and Sweden. Both countries developed victim compensation programs located within welfarist administrative institutions, suggesting common penal welfare frameworks and instruments. Using the comparative historical case study method, the study finds that formative victim compensation policies in the two countries differed widely, reflecting social welfare versus remedial welfare policies, and rehabilitative versus punitive carceral frameworks, respectively. Arguments upholding penal welfarist ideals and social insurance concerns underlay the early formation of Sweden’s victim compensation program and anchored subsequent developments while, in the United States, political conditions led to a rapid trajectory in more punitive directions.